posted by Shreya on .
solve equation |x^2-2x-6| using quadratic formula. i not get how to do this and it says quadratic formula.
you cannot solve it since you cant square root a negative number... unless -2x was positive 2x.
sorry i missing part of question whole question be |x^2-2x-6| = 4. and answer have to be 1+-sqrt3, 1+-sqrt11 i just not get how to get this.
f(x) = x^2 - 2x - 6 has roots 1±√7 = -1.65,3.65
Between the roots, f(x) < 0 and we have
-(x^2-2x-6) = 4
x^2 - 2x - 2 = 0
x = 1±√3
both those values are in the interval, so they're ok as solutions
Outside that interval,
x^2-2x-6 = 4
x^2 - 2x - 10 = 0
x = 1±√11
both those values are outside the interval, so they're ok as solutions